Flora of kurgans in the Pontic herb(-rich) grass steppe zone in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The results of study of floristic diversity of kurgans in the Pontic herb(-rich) grass steppe zone (according to MAP OF THE NATURAL VEGETATION OF EUROPE 2000: the west and central Pontic herb-grass steppe (M5) and west and central Pontic herb-rich grass steppe (M1) zones) in Mykolaiv and Kirovograd Regions, are presented. Twenty-nine kurgans higher than 3 m, distributed over an area approx. 9000 km2, were surveyed. The investigated kurgan flora contains more species than the flora of the barrows in the west Pontic grass steppe and desert steppe zones, being estimated at 439 species. The number of species on a single kurgan varied from 89 to 171 with 125,5 on average. Hemicryptophytes dominated in the kurgan flora (38,8%) of the Pontic herb(-rich) grass steppe zone, whereas therophytes prevailed in barrow flora in the steppe zones southwards. Phanerophytes were more numerous as well (8,7%). (Annuals and biennials constituted 35,1% of the kurgan flora. Most of them are synanthropic species, e.g. weeds derived from the surrounding fields. The total number of alien species (anthropophytes) reached 113. Archaeophytes and kenophytes comprised 23,5% of the kurgan flora. A total of 19 syntaxa of higher rank were represented in all the kurgans studied. Species associated with steppe syntaxa such as Festuco-Brometea, Festucetea vaginatae, Polygono- Artemisietea and Galietalia veri comprised as much as 49,9 % of the kurgan flora. As in the case of the desert and grass steppes, species belonging to classes Festuco-Brometea and Stellarietea mediae were predominant in the herb rich grass steppe, which also confirmed the semi-natural character of the kurgan flora. The species of particularly high floristic value were: Adonis vernalis, Amygdalus nana, Anemone sylvestris, Astragalus dasyanthus, Crocus reticulatus, Elytrigia stipifolia, Galium volhynicum, Goniolimon tataricum, Hesperis tristis, Iris halophila, Limonium platyphyllum, Linaria biebersteinii, Ornithogalum kochii, Phlomis hybrida, Stipa capillata, S. lessingiana. The investigations carried out in the Pontic herb(-rich) grass steppe zone confirm that kurgans constitute refugia for the steppe flora. They are more or less uniformly distributed in the steppe zone, and could play an important role in the local restoration of the natural plant cover. Therefore, they should be put under protection as archeological and nature monuments.
Keywords: barrows, refugia of steppe flora, floristic diversity, herb-grass steppe, herb-rich grass steppe, protection of kurgans, the South of Ukraine.